IN SEARCH OF NEW OPPORTUNITIES: THE INDONESIANISASI OF ECONOMIC LIFE IN YOGYAKARTA IN THE 1950s - Bambang Purwanto (Masyarakat Indonesia, 2013)
A flourishing study on Indonesias economic history in the last two decades has stillbeen unable to change a general impression of limited role of the indigenous peoplein economic activities during modern times. The transformation of the Indonesianeconomy from a colonial economy to a national economy through the process ofIndonesianisasi, went through different historical patterns. The independent Indonesiadid not translate the idea of political nationalism directly into economic prosperityuntil the late 1950s. As a result, there is always only a small portion of independententrepreneurs among the population, namely those who are supposed to run the publiceconomy smoothly without political intervention. This paper provides theoreticalconsiderations and historical facts on the process of Indonesianisasi. It discusses theeconomic life of people in Yogyakarta, the capital city Republic of Indonesia duringthe war of independence, soon after the recognition of Indonesias independence inDecember 1949.Keywords: Indonesianisasi, Colonial period, Foreign domination, Yogyakarta